First report of hypoplastic left heart syndrome in 3p- syndrome and review of candidate genes - Ana Kalise Böttcher; Monique Banik Siqueira; Natasha Malgarezi; Marcela Rodrigues Nunes; Rafaella Mergener; Luisa Pigatto Kalil; Patrícia Trevisan; Paulo Ricardo Gazzola Zen (Revista Paulista de Pediatria)
ABSTRACT Objective: 3p deletion syndrome is a rare monosomal disease that encompasses deletions throughout the short arm of chromosome 3. It is often in the distal region (3p25-pter), but variations in breakpoints and a complex clinical manifestation exist, with congenital heart defects being considered rare. We present the first case of hypoplastic left heart syndrome and minor dysmorphic features associated with 3p- syndrome. Furthermore, we aim to establish a gene-phenotype association. Case description: The diagnosis was made by karyotyping, followed by a literature investigation and in silico bioinformatic analysis about the possible candidate genes associated with congenital heart defects or hypoplastic left heart syndrome in 3p- syndrome. All genes analyzed that could affect heart formation are located in the 3p25.3 region, adjacent to the deleted region in the newborn from our case (3p26). Taking into account the technical limitations of the karyotype and the strength of evidence from each gene evaluated and locus proximity, it is likely that an unidentified partial break in the CAV3 gene occurred. Comments: We identified an indirect relation between gene CAV3 and hypoplastic left heart syndrome due to its strong association with cardiomyopathies and isolated cardiac defects. Furthermore, the cytogenetic band from our case is new information for the delimitation of a critical cardiac region on 3p syndrome, a discussion that has been ongoing since 1986. Thus, we reinforce the importance of cytogenetic investigation in patients with hypoplastic hearts and dysmorphia, assisting in diagnosis, definition of prognosis, and genetic counseling for the family.